Outbreak of bloodstream infection with extendedspectrum ß-lactamase-producing Klebsiella pneumoniae at a Teaching Hospital - Senanayake, NP; Karunanayake, L (Journal of Nepal Paediatric Society, 2015)
Introduction: Klebsiella pneumoniae (K. pneumoniae) is an important hospital-acquired pathogen causing severe infections in neonatal units. Several outbreaks of infection caused by multi-drug-resistant K. pneumoniae isolates have been widely reported among neonates. The aim is to investigate an outbreak of blood stream infection caused by Extended-Spectrum ß-Lactamases (ESBL) producing K.pneumoniae in a Neonatal Intensive Care Unit (NICU) at Teaching Hospital Kandy, Sri Lanka. Materials and Methods: Blood culture samples were collected from the neonates on admission to the NICU and 2 to 3 days later on clinical suspicion of blood stream infection. The blood culture samples were processed according to the standard methods and the antibiotic susceptibility tests were carried out as per Clinical Laboratory Standards Institute (CLSI) guidelines. Results: Of the 140 blood cultures 36 were identified as Extended-Spectrum ß-Lactamases (ESBL) producing K.pneumoniae. All the isolates were susceptible to ciprofloxacin, amikacin, netilmicin, imipenem and meropenem. Twenty eight of the 36 patients responded to treatment with a combination of amikacin and meropenem. Conclusion: ESBL producing K.pneumoniae was responsible for this outbreak at the NICU. Knowing the susceptibility patterns of clinical isolates will allow the rational use of antibiotics, which is important in the treatment of infections with multi-drugresistant bacteria. J Nepal Paediatr Soc 2014;34(3):230-232 DOI: http://dx.doi.org/10.3126/jnps.v34i3.10459